Latihan Super Garuda Shield dalam Perspektif Balance of Power di Indo-Pasifik - Irgi Mukramin Paisal; Agussalim Burhanuddin (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The Indo-Pacific region, being vast and full of potential, has become an arena for complex geopolitical competition among major powers. This article analyzes the Super Garuda Shield Exercise as an important instrument in responding to those dynamics. Using the approach of the balance of power theory and defense diplomacy, this article discusses the Super Garuda Shield exercise as an instrument of the balance of power in great power competition and its role as a tool of Indonesia's defense diplomacy. The research results show that the Super Garuda Shield exercise is an important instrument in the balance of power strategy in the region. Through this defense cooperation, Indonesia seeks to balance China's growing influence without getting trapped in a formal alliance. This demonstrates how Indonesia implements an independent-active foreign policy and its proactive role as a middle power in maintaining regional stability. This article emphasizes the importance of collaboration and coordination to establish a regional security order that is adaptive to increasingly complex geopolitical dynamics.